Three new Asiatic species of Hyadaphis (Hemiptera, Aphididae) - Nafría, Juan M. Nieto; Hidalgo, Nicolas Pérez; Brown, Paul A. (Zootaxa, 2016)
Three new species of Hyadaphis Kirkaldy, 1904 (Hemiptera, Aphididae, Macrosiphini) are established: Hyadaphis levantina sp. n. from specimens caught on Lonicera nummulariifolia from Lebanon and Israel, and Hyadaphis anethi sp. n. plus Hyadaphis parva sp. n. from specimens respectively caught on Anethum sp. and Andrachne (?) cordifolia from Pakistan. Apterous viviparous females of all three species, alate viviparae of the first two and males of H. anethi are described. Known and new species of Hyadaphis are grouped for two relevant characters: (1) size and shape of siphunculi, and (2) host plant and life cycle; and the discriminant features of apterous viviparous females of the new species are compared with the already described species of the same group and a key for the Hyadaphis species is provided.